A comparison study of the degradative effects and safety implications of UVC and 405 nm germicidal light sources for endoscope storage. (November 2016) - Irving, Daniel; Lamprou, Dimitrios A.; Maclean, Michelle; MacGregor, Scott J.; Anderson, John G.; Grant, M. Helen
Abstract: Storage of flexible endoscopes under germicidal ultraviolet (UVC) light has been associated with degradation of device material leading to failure and increased risk to patients. 405 nm germicidal light presents a possible alternative, potentially providing effective bacterial inactivation without material damage. Samples of endoscope material were exposed to UVC and 405 nm germicidal light sources and a broad spectrum light source control. Material properties were monitored using FTIR, AFM, contact angle and confocal microscopy. Significant changes were observed with samples exposed to the UVC source, with variations in FTIR spectra indicative of side chain scission, a decrease in contact angle from 82.6° to 61.4°, an increase in average surface roughness from 2.34 nm to 68.7 nm and visible cracking of the surface. In contrast samples exposed to the 405 nm light source showed little to no changes, with any variations being comparable to those seen on samples exposed to the broad spectrum control. Bacterial adhesion tests on samples showed an 86.8% increase in Pseudomonas aeruginosa adhesion on UVC exposed samples and no significant increase in adhesion with samples exposed to the other light sources. 405 nm germicidal light therefore potentially represents a safer alternative to UVC light for use in flexible endoscope storage.